Short- and long-term cognitive effects of chronic cannabinoids administration in late-adolescence rats. - Hila Abush (Public Library of Science (PLoS), 2012)
The use of cannabis can impair cognitive function, especially short-term memory. A controversial question is whether long-term cannabis use during the late-adolescence period can cause irreversible deficits in higher brain function that persist after drug use stops. In order to examine the short- and long-term effects of chronic exposure to cannabinoids, rats were administered chronic i.p. treatment with the CB1/CB2 receptor agonist WIN55,212-2 (WIN; 1.2 mg/kg) for two weeks during the late adolescence period (post-natal days 45-60) and tested for behavioral and electrophysiological measures of cognitive performance 24 hrs, 10 and 30 days after the last drug injection. The impairing effects of chronic WIN on short-term memory in the water maze and the object recognition tasks as well as long-term potentiation (LTP) in the ventral subiculum (vSub)-nucleus accumbens (NAc) pathway were temporary as they lasted only 24 h or 10 d after withdrawal. However, chronic WIN significantly impaired hippocampal dependent short-term memory measured in the object location task 24 hrs, 10, 30, and 75 days after the last drug injection. Our findings suggest that some forms of hippocampal-dependent short-term memory are sensitive to chronic cannabinoid administration but other cognitive impairments are temporary and probably result from a residue of cannabinoids in the brain or acute withdrawal effects from cannabinoids. Understanding the effects of cannabinoids on cognitive function may provide us with tools to overcome these impairments and for cannabinoids to be more favorably considered for clinical use.